Correlation of Self Perception Towards The Practice of Teaching Skills With Pedagogical Competence Knowledge of Eduacational Culinary Arts Students at Jakarta State University - Tsabita, Vanadia Ayu; Febriana, Rina; Yulianti, Yeni (Jurnal Ilmiah Wahana Pendidikan, 2025)
The aim of this study is to analyze the correlation between self-perception of teaching skills practice and pedagogical competency knowledge among Culinary Education students at Universitas Negeri Jakarta. his study was conducted at Campus A of Universitas Negeri Jakarta from December 2022 to December 2024. The sample was determined using purposive sampling and calculated with the Slovin formula. The research method used was a survey method through descriptive analysis, Spearman rank correlation, significance testing, and the coefficient of determination.The study found that students' self-perception of teaching skills practice falls into the "good" category. Meanwhile, their knowledge of pedagogical competence is classified as "moderate." The relationship analysis using Spearman correlation showed a correlation value of 0.808, with a significance test (Z-score) of 5.94 > 1.96. This indicates a significant positive medium correlation between self-perception of teaching skills practice and knowledge of pedagogical competence. Self-perception of teaching skills practice contributes 65% to the pedagogical competence knowledge of Culinary Education students at Universitas Negeri Jakarta.